Endotoxin induced muscle wasting in avian and murine skeletal muscle - Tarabees, Reda Zakaria Ibrahim (2011)
This project was aimed to elucidate the sub-cellular and molecular regulation of Lipopolysaccharide (LPS) induced muscle protein turnover (protein synthesis (PS) and protein degradation) in two in vitro models, C2C12 murine myotubes and avian primary skeletal muscle cell line. In addition, the effect of natural challenge of chicken with Salmonella serotypes gallinarium or Enteritidis on mRNA expression levels in skeletal muscle was assessed. LPS (1 μgml-1) transiently decreased PS rate by 50% compared with control cells. This effect was mediated via decreased phosphorylation of translation initiation mediators (p70S6K, 4E-BP1 and eIF-4E). This effect was preceded by decreased Akt and mTOR phosphorylation. Although, LPS significantly increased p38, Erk1/2 and their down stream target Mnk1, however, this effect was not sufficient to abolish LPS-induced decreased PS. The role of Akt and MAPKs (p38 or Erk1/2) was verified using specific pathway inhibitors. Inhibition of Akt by LY0294002 (PI3-K/Akt inhibitor) dramatically decreased PS by 80% compared with control cells. Incubation of C2C12 myotubes with SB203580 (p38 inhibitor) or with PD098059 (MEK/Erk inhibitor) alone significantly decreased the PS rate at the 3 h time point by -63  12.48% and -64  5.05% respectively compared with control cells (P < 0.01). In contrast, LPS (1 μgml-1) significantly increased the chymotrypsin-like enzyme at all the time points. This effect was preceded by a significant increase in the IkB-α phosphorylation and nuclear translocation of NF-kB, and significant increase in TNF-α, atrogin-1, MuRF1 and TLR4 mRNA expression. Of note, increased atrogin-1 mRNA is the prominent feature of our septic model. The data presented in chapter 4 and 5 showed that, there is no absolute correlation between the expression levels of atrogens (atrogin-1 and MuRF1) and the overall proteolytic activity in LPS-stimulated C2C12 myotubes. The beneficial roles of the curcumin were evaluated LPS-stimulated C2C12 myotubes for 3 h. Incubation of C2C12 myotubes with LPS (1 μgml-1) and curcumin (25 μM) significantly decreased the LPS-induced chymotrypsin-like enzyme activity. This effect was mediated via decreased p38 and IkB-α phosphorylation. Although, curcumin blocked LPS-induced decreased Akt and p70S6K phosphorylation and significantly increased Erk1/2 phosphorylation, however, curcumin still had no effect on LPS-induced decreased protein synthesis. The effect of the LPS on the muscle protein turnover in the avian primary skeletal muscle was summarised in chapter (7). Incubation of avian primary skeletal cells with LPS (1 μgml-1) for 3 h, significantly decreased the proteasomal activity and increased PS rate. The difference in response to LPS between C2C12 myotubes and avian primary skeletal muscle cells could be attributed to the different incubation parameters mainly the presence of insulin in case of avian primary cells. Finally, the effect of natural challenge of chicken with S. Gallinarum or S. Enteritidis on skeletal muscle mRNA expression was summarised in chapter 9. Natural challenge of chicken with S. Gallinarum or S. Enteritidis had no effect on the expression of many atrophic genes in chicken skeletal muscle (gastrocnemius and pectoral muscle). The data collected from this project showed that, LPS is a strong catabolic stimulus significantly decreased PS along with increased protein breakdown rates in skeletal muscle. This effect was mediated via two main pathways PI3-K/Akt and MAPKs (p38 or Erk1/2) and the cross talk between them is exists. The better understanding of these signalling cascades and their cross talk will be the starting point for developing the appropriate and safe therapeutic intervention in order to decrease the sepsis-induced muscle proteolysis.